2023
DOI: 10.1186/s12882-023-03204-3
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic nephropathy with marked extra-capillary cell proliferation: a case report

Abstract: Background Extra-capillary hypercellularity is a common finding in crescentic glomerulonephritis (GN) and focal segmental glomerulosclerosis (FSGS). In diabetic nephropathy (DN), extra-capillary hypercellularity is often observed as a finding of complications such as IgA nephropathy or microscopic polyangiitis superimposed on DN. However, in rare cases, epithelial cell proliferation may accompany DN. We experienced a case of nodular diabetic glomerulosclerosis with marked extra-capillary hyperc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Because of our findings regarding the role of the Sirt1/Claudin-1 axis on podocyte function, many other reports have shown that depressed Sirt1 and amplified Claudin-1 were detectable in damaged podocytes in DN [ 10 , 11 ] and in other kidney diseases such as focal segmental glomerulosclerosis [ 12 , 13 ] and hypertension-induced glomerular sclerosis [ 14 ]. In this regard, the regulatory mechanism by which repressed Sirt1 augmented Claudin-1 is considered significant for establishing the potential of diagnostic markers and/or therapeutic targets of the Sirt1/Claudin-1 axis in kidney diseases [ 15 , 16 ]. This is explained in more detail in the following section.…”
Section: Changes In Sirt1 and Nmn In The Very Early Stages Of Dnmentioning
confidence: 99%
“…Because of our findings regarding the role of the Sirt1/Claudin-1 axis on podocyte function, many other reports have shown that depressed Sirt1 and amplified Claudin-1 were detectable in damaged podocytes in DN [ 10 , 11 ] and in other kidney diseases such as focal segmental glomerulosclerosis [ 12 , 13 ] and hypertension-induced glomerular sclerosis [ 14 ]. In this regard, the regulatory mechanism by which repressed Sirt1 augmented Claudin-1 is considered significant for establishing the potential of diagnostic markers and/or therapeutic targets of the Sirt1/Claudin-1 axis in kidney diseases [ 15 , 16 ]. This is explained in more detail in the following section.…”
Section: Changes In Sirt1 and Nmn In The Very Early Stages Of Dnmentioning
confidence: 99%
“…When this barrier is disturbed by PEC injury, its permeability increases, possibly resulting in interstitial inflammation subsequent to periglomerular leakage of filtered protein. PECs are also involved in the formation of crescents [17][18][19], so claudin1-positive cells are expected to be excreted in the urine of patients with glomerular crescents.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of glomerular crescents is a characteristic feature of rapidly progressive glomerulonephritis and can be observed in the severe forms of various types of glomerulonephritis, including postinfectious glomerulonephritis, membranoproliferative glomerulonephritis, lupus nephritis, and immunoglobulin A nephropathy [14][15][16]. While glomerular crescents have primarily been identified in the acute form of glomerulonephritis, there have been reports of their occurrence in isolated cases of DKD [17][18][19][20][21]. Some single-center cohort studies have examined the relationship between glomerular crescents and a poorer kidney prognosis in patients with type 2 DKD [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%